Intercellular propagation of extracellular signal-regulated kinase activation revealed by in vivo imaging of mouse skin - Hiratsuka, Toru; Fujita, Yoshihisa; Naoki, Honda; Aoki, Kazuhiro; Kamioka, Yuji; Matsuda, Michiyuki (eLife, 2015)
Extracellular signal-regulated kinase (ERK) is a key effector of many growth signalling pathways. In this study, we visualise epidermal ERK activity in living mice using an ERK FRET biosensor. Under steady-state conditions, the epidermis occasionally revealed bursts of ERK activation patterns where ERK activity radially propagated from cell to cell. The frequency of this spatial propagation of radial ERK activity distribution (SPREAD) correlated with the rate of epidermal cell division. SPREADs and proliferation were stimulated by 12-O-tetradecanoylphorbol 13-acetate (TPA) in a manner dependent on EGF receptors and their cognate ligands. At the wounded skin, ERK activation propagated as trigger wave in parallel to the wound edge, suggesting that ERK activation propagation can be superimposed. Furthermore, by visualising the cell cycle, we found that SPREADs were associated with G2/M cell cycle progression. Our results provide new insights into how cell proliferation and transient ERK activity are synchronised in a living tissue.
Keywords: in vivo imaging; ERK; epidermis; cell cycle